2023
DOI: 10.1371/journal.pone.0278300
|View full text |Cite
|
Sign up to set email alerts
|

Fit for purpose of on-the-road driving and simulated driving: A randomised crossover study using the effect of sleep deprivation

Abstract: Introduction Drivers should be aware of possible impairing effects of alcohol, medicinal substance, or fatigue on driving performance. Such effects are assessed in clinical trials, including a driving task or related psychomotor tasks. However, a choice between predicting tasks must be made. Here, we compare driving performance with on-the-road driving, simulator driving, and psychomotor tasks using the effect of sleep deprivation. Method This two-way cross over study included 24 healthy men with a minimum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The intervention to deprive subjects of sleep was successful, as observed from the KSS (sleepiness) and LSEQ (early morning behaviour) questionnaire results. While sleep deprivation significantly reduces attention and vigilance, 31 this likely did not bias results as others have discussed previously. 11 In case of reduced attention, a parallel shift in pain detection and tolerance is expected, plausibly on each pain modality in approximately the same manner.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The intervention to deprive subjects of sleep was successful, as observed from the KSS (sleepiness) and LSEQ (early morning behaviour) questionnaire results. While sleep deprivation significantly reduces attention and vigilance, 31 this likely did not bias results as others have discussed previously. 11 In case of reduced attention, a parallel shift in pain detection and tolerance is expected, plausibly on each pain modality in approximately the same manner.…”
Section: Discussionmentioning
confidence: 62%
“…A young age range was included as this study was part of a larger study in which we also assessed the effects of TSD on driving performance. 31 Recruiting older subjects for that test was considered unsafe. We did not correct for multiple statistical testing, which may have led to false positives in our results.…”
Section: Discussionmentioning
confidence: 99%
“…The between-group factor was driver group (sleep deprivation or control) and the within-group factor was hazard type (covert hazard or overt hazard). Based on previous research [4,10] on sleep deprivation for the purpose of the present study, sleep deprivation was defined as sleep restriction for at least 24 h (≥24 h awake), and drivers in the control group maintained a normal daily amount of sleep.…”
Section: Experimental Designmentioning
confidence: 99%
“…Numerous studies found that sleep deprivation and poor sleep quality among drivers lead to increased accident risk [4,[7][8][9]. Sleep deprivation refers to the deprivation of being unable to meet normal sleep requirements due to personal or work reasons [4,10,11]. Under sleep deprivation conditions, variation in the drivers' lateral position in a lane increases [12], and the frequency of lane departures [11,13] and velocity variability increase [14].…”
Section: Introductionmentioning
confidence: 99%